An Empirical Study of Empirical Legal Scholarship: The Top Law Schools - George, Tracey E. (2006)
Empirical legal scholarship is arguably the most significant emerging intellectual movement. Empirical legal scholarship (ELS), as the term is generally used in law schools, refers to a specific type of empirical research: a model-based approach coupled with a quantitative method. This paper ranks law schools based on their place in the ELS movement and offers an essential ranking framework that can be adopted for other intellectual movements. A revised version of the paper was posted on October 11. The updated tables reflect additional data